The Predictor Of Emotional Regulation On Academic Procrastination - Sinta, Tri; Sugiyo, Sugiyo; Sunawan, Sunawan (Jurnal Bimbingan Konseling, 2022)
Academic procrastination can hinder students to progress. This study aimed to examine the impact of emotional regulation on academic procrastination. It involved 300 students from three public senior high school in Tebing Tinggi sub-district, South Sumatera. In collecting the data, the researchers used APS (Academic Procrastination Scale) and ERQ (Emotion Regulation Questionnaire) instruments. Based on the findings, it was known that there was a negative correlation between emotional regulation and academic procrastination. Thus, this study recommends the importance of emotional regulation to reduce academic procrastination.